Using the French LPIS database to highlight farm area dynamics: The case study of the Niort Plain. (April 2018) - Barbottin, Aude; Bouty, Clémence; Martin, Philippe
Highlights: An analysis of farm area dynamics was performed for a continuous time period in a sensitive area in South-West France. The enlargement of farm field patterns was identified as an important dynamic. Farm enlargement was associated with a slight increase in land fragmentation. Most of the farms displayed changes in area, but the total amount of land transferred from one farm to another was limited. Our results should help planners to identify the patterns of farm dynamics in their regions. Abstract: Decreases in the number of farms over the last decade have led to an increase in mean farm size and a fragmentation of the land on the remaining farms. These changes can influence the management of cropping systems by farmers, generally leading to a decrease in crop diversity at the landscape scale and a homogenization of agricultural practices between fields, to reduce logistic costs. At the landscape scale, these changes can modify agricultural pressure on natural resources (e.g. water, soil, biodiversity), by creating hotspots of fields subject to intensive management. Consequently, natural resource management, mostly at the local scale, requires new monitoring tools dedicated to local farm dynamics. This work aimed to characterize farm area dynamics between 2007 and 2013 on the Niort Plain, a sensitive area located in the South-West of France that is subject to water and biodiversity issues. Changes in farm area were characterized, taking into account not only farm size, but also the spatial distribution of the islets included in the land pattern. The LPIS database, which provides quasi-continuous broad coverage of the French agricultural areas, was used to analyze changes in farm area, through characterization of the annual changes in farm area and their effects in terms of land fragmentation and farm size distribution. Six types of farm area dynamics were characterized: the enlargement of farms with and without a reconfiguration of the land use pattern, a decrease in the utilized agricultural area (UAA) of farms with and without a reconfiguration of the land use pattern, and a stable UAA with and without reconfiguration of the land use pattern. We found that 5.5% of the farms were either split into smaller units or stopped seeking CAP subsidies during the period considered. Two patterns predominated: a stable farm area and enlargement of the farm area. Farms of many different initial sizes displayed enlargement, generally through the acquisition of islets from another farm that was split up. Farm dynamics had a limited impact on the fragmentation of farm land. Farm enlargement led to a slight increase in the dispersion of islets from the farm center. The procedure developed here for the characterization of farm area dynamics is particularly suitable for application at the temporal scales used by planners working on environmental programs. By monitoring farm area dynamics, planners could also set specific devices to enable them to focus either on the total number of farms or exclusively on a subset of farms of strategic importance for the management of natural resources due to their area dynamics, location or aggregation in the environment.